Physical Exercise and Immune System: Perspectives on the COVID-19 pandemic - Improta-Caria,Alex Cleber (2021)
Physical exercise training (PET) has been considered an excellent non-pharmacological strategy to prevent and treat several diseases. There are various benefits offered by PET, especially on the immune system, promoting changes in the morphology and function of cells, inducing changes in the expression pattern of pro and anti-inflammatory cytokines. However, these changes depend on the type, volume and intensity of PET and whether it is being evaluated acutely or chronically. In this context, PET can be a tool to improve the immune system and fight various infections. However, the current COVID-19 pandemic, caused by SARS-CoV-2, which produces cytokine storm, inducing inflammation in several organs, with high infection rates in both sedentary and physically active individuals, the role of PET on immune cells has not yet been elucidated. Thus, this review focused on the role of PET on immune system cells and the possible effects of PET-induced adaptive responses on SARS-CoV-2 infection and COVID-19.